Sosialisasi Parenting: Pentingnya Digital Parenting untuk Mendidik Anak di Era Digital - Idrus, Muhammad Ainun; Ahmad, Andi; Pasalli, Hastria; Andini, Andini; Misraeni, Misraeni; Zahra, Fatimatus; Witri, Witri; Audy, Audy; Taufiq, Taufiq; Herdiana, Besse (IKIP PGRI Bojonegoro, 2025)
ABSTRACTThis discussion or outreach aims to educate the public about the importance of taking action or implementing rules and monitoring the use of technology. Digital parenting is a way to care for children in the digital or technological era. The method for implementing parenting outreach with the theme